Sex‐ and age‐specific incidence of healthcare‐register‐recorded eating disorders in the complete swedish 1979–2001 birth cohort. Issue 8 (December 2015) - Javaras, Kristin N.; Runfola, Cristin D.; Thornton, Laura M.; Agerbo, Esben; Birgegård, Andreas; Norring, Claes; Yao, Shuyang; Råstam, Maria; Larsson, Henrik; Lichtenstein, Paul; Bulik, Cynthia M.
ABSTRACT: Objective: To investigate the sex‐ and age‐specific incidence of healthcare‐register‐recorded anorexia nervosa (AN) and other eating disorders (OED) in a complete birth cohort, and assess whether incidence varies by diagnostic period and (sub‐) birth cohort. Method: We used the actuarial method and Poisson models to examine the incidence of AN and OED from 1987 to 2009 (when individuals were 8–30 years old) for a cohort of 2.3 million individuals (48.7% female) born from 1979 to 2001 in Sweden, identified using Swedish registers. Results: For both sexes, incidences of AN and OED increased considerably for diagnostic periods after 2000, but differed little by birth cohort. In 2009, AN incidence in the peak age category was 205.9 cases/100, 000 persons (95% CI: 178.2, 233.5) for females (14–15 years), versus 12.8 cases/100, 000 (95% CI: 5.6, 20.1) for males (12–13 years). OED incidence in the peak age category was 372.1 cases/100, 000 (95% CI: 336.4, 407.9) for females (16–17 years), versus 22.2 cases/100, 000 (95% CI: 13.3, 31.1) for males (14–15 years). Discussion: Our finding of an increase in healthcare‐register‐recorded eating disorders for diagnostic periods after 2000 likely reflects improved detection and expanded register coverage in Sweden. The peak of eating disorder incidence in adolescence, which began unexpectedly early for AN in males, suggests the importance of vigilance for signs of AN in young boys and early primary prevention efforts. Waiting until later could miss critical windows for intervention that could prevent disorders from taking root. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:1070–1081).